1990
DOI: 10.1172/jci114688
|View full text |Cite
|
Sign up to set email alerts
|

Impaired vasodilation of forearm resistance vessels in hypercholesterolemic humans.

Abstract: The effect of hypercholesterolemia on vascular function was studied in humans. To eliminate the potential confounding effects of atherosclerosis, vascular reactivity was measured in the forearm resistance vessels of 11 normal subjects (serum LDL cholesterol = 111±7 mg/dl) and 13 patients with hypercholesterolemia (serum LDL cholesterol = 211±19 mg/dl, P < 0.05). Each subject received intrabrachial artery infusions of methacholine, which releases endothelium-derived relaxant factor, and nitroprusside which dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
466
5
16

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 975 publications
(509 citation statements)
references
References 36 publications
22
466
5
16
Order By: Relevance
“…Resistance vessel function in the forearm is assessed by strain-gauge venous impedance plethysmography. This methodology examines the change in forearm blood flow in response to direct intra-arterial (brachial artery) administration of agonists (62). This technique is excellent for acute interventions with repeated measurements.…”
Section: Methods Of Assessing Endothelial Functionmentioning
confidence: 99%
“…Resistance vessel function in the forearm is assessed by strain-gauge venous impedance plethysmography. This methodology examines the change in forearm blood flow in response to direct intra-arterial (brachial artery) administration of agonists (62). This technique is excellent for acute interventions with repeated measurements.…”
Section: Methods Of Assessing Endothelial Functionmentioning
confidence: 99%
“…16,17 Under conditions of BH 4 deficiency, electron flow from the reductase domain to the oxidase domain is diverted to molecular oxygen rather than to L-arginine, a substrate of NO, leading to eNOS uncoupling. In this condition, uncoupled eNOS produces superoxide rather than NO.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…8 A great number of studies have shown that aging and hypertension are associated with impairment of endothelium-dependent vascular relaxation in coronary, forearm and renal arteries, and endothelial dysfunction, which is involved in the development of atherosclerosis, was found to increase the risk of cardiovascular and cerebrovascular diseases. [9][10][11][12][13][14][15][16][17] It is expected that improvement or augmentation of endothelial function will prevent the development of atherosclerosis, resulting in reduction in cardiovascular and cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that impaired endothelium-dependent and -independent vasodilation in patients with ED is similar to that of patients with hypercholesterolemia. 40 In addition, some studies have shown that hypercholesterolemia results in an increase in sympathetic activity. 41 Current medical treatments for ED, such as PDE5 inhibitors, are palliative.…”
Section: Atorvastatin In Sildenafil Nonresponders F Dadkhah Et Almentioning
confidence: 99%